We The Divided: Partitions of Performance in the Ceramic State - Read, Alan (Archīum Ateneo, 2024)
The common association between theater and community is here inverted to explore the relationship between theatrical practice and immunity, or “affects of adjustment” between spectator and event. Drawing upon Roberto Esposito’s figuring of relations between community and immunity, on Jacques Ranciere’s propositions of the “emancipated spectator” and the part of those who have no part,” and Gerald Raunig’s conception of “Division” from his work on the Dividuum (2016), this essay examines a sequence of case studies central to the author’s own practiced experiences: Rotherhithe Theatre Workshop in the 1980s, Transhumance in the 1990s, and the Performance Biennial Athens in 2016. The dynamic here is to track an increasing scepticism about the social claims made for theater and ways of discussing performance that do not surrender to pseudo action in the absence of political commitment and change. The essay concludes amongst the Greek Attic Kraters of the 5th century BCE, curated from the Liverpool Museums at Tate Liverpool, contesting that the “ceramic state” continues at the interface between the continual promise of immersion and material histories of exclusion from the scene.